Crystallization and preliminary X-ray analysis of three dUTPases from Gram-positive bacteria - Li, Gui-Lan (International Union of Crystallography, 2009)
All organisms examined to date possess a dUTPase that performs the important function of efficiently hydrolyzing dUTP to dUMP in order to prevent the incorporation of dUTP into DNA. Three putative dUTPases from Gram-positive bacteria have been studied in this work. Two dUTPase-encoding genes, yncF and yosS, have been identified in Bacillus subtilis. The gene dut, encoding dUTPase from the dental pathogen Streptococcus mutans, was amplified from S. mutans genomic DNA. The three genes were cloned into expression vectors and overexpressed at high levels in Escherichia coli. Each protein was purified in two steps using chromatographic methods. Crystals of the YosS and YncF proteins and of S. mutans dUTPase were obtained using the vapour-diffusion method. X-ray diffraction data sets were collected from crystals of selenomethionine-labelled YosS and S. mutans dUTPase to resolutions of 2.3 and 1.7 Å, respectively. The crystal of native YncF diffracted to 2.7 Å resolution.